Konseling Traumatik Dalam Pendidikan Islam - Tanjung, Ifnaldi (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2023)
Indonesia is one of the countries that is often hit by natural disasters, and many of these disasters cause many victims. And many survivors experienced psychological trauma. In this study the authors used a literature review approach, namely conducting an assessment of the literature related to counseling guidance from various sources. Traumatic counseling is counseling that is held in order to help counselees who experience traumatic events, so that counselees can get out of the traumatic events they have experienced and can take lessons from these traumatic events. The forms of services provided to clients who experience trauma are (1) information services, (2) individual counseling services, (3) group counseling services and (4) group counseling services.